2017
DOI: 10.1149/2.f08174if
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoferrites for RF CMOS: Enabling 5G and Beyond

Abstract: The upcoming 5th generation (5G) telecommunication technology will enable realization of the full potential of the Internet-of-things (IoT) by utilizing various frequency bands, ranging from <4 GHz to 100 GHz. A brief review of the technical requirements of RF CMOS at the unveiling of the 5G system is provided. Key challenges associated with 5G are illustrated, with a focus on the need for, and state of the art of, magnetic materials, especially ferrites, in enhancing the performance of RF integrated circuits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Recently, Saha et al synthesized [52] nano hollow spheres (NHSs) (shown in Figure 9a) instead of nanoparticles of Zn y Fe 3−y O 4 by template-free solvothermal method, which shows an increase in M S values with Zn doping, attaining a maximum at x = 0.2 (Ms = 92.52 emu/g at 300 K), similarly to the bulk Zn y Fe 3−y O 4 . Therefore, enhanced magnetism with a decrease in conductivity, permittivity, and dipolar interaction enables Zn y Fe 3−y O 4 NHSs to be a useful material for high-frequency applications [39,[53][54][55][56][57]. Porous ZnFe2O4 nanotubes (Figure 9b) have been fabricated by electrospinning followed by two-step calcination in the atmosphere [58].…”
Section: Other Nanostructured Znfe 2 O 4 Geometriesmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Saha et al synthesized [52] nano hollow spheres (NHSs) (shown in Figure 9a) instead of nanoparticles of Zn y Fe 3−y O 4 by template-free solvothermal method, which shows an increase in M S values with Zn doping, attaining a maximum at x = 0.2 (Ms = 92.52 emu/g at 300 K), similarly to the bulk Zn y Fe 3−y O 4 . Therefore, enhanced magnetism with a decrease in conductivity, permittivity, and dipolar interaction enables Zn y Fe 3−y O 4 NHSs to be a useful material for high-frequency applications [39,[53][54][55][56][57]. Porous ZnFe2O4 nanotubes (Figure 9b) have been fabricated by electrospinning followed by two-step calcination in the atmosphere [58].…”
Section: Other Nanostructured Znfe 2 O 4 Geometriesmentioning
confidence: 99%
“…Performance of on-chip X-band (8–12 GHz) inductor, integrated with magnetic film can enhance its inductance density as well as the quality factor, facilitating miniaturization of RF devices and reducing dependency on silicon [ 54 , 55 , 56 ]. To find a suitable candidate material, whose ferromagnetic resonance frequency ( f FMR ) is above 6 GHz, i.e., in the expected new spectrum for 5G mobile communication, is now indispensable.…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations